Green warriors : Army environmental considerations for contingency operations from planning through post-conflict - Mosher, David E.; Lachman, Beth E., 1960-; Greenberg, Michael D.; Nichols, Tiffany; Rosen, Brian; Willis, Henry H.; Arroyo Center. Strategy, Doctrine, and Resources Program; Rand Corporation; U.S. Army Environmental Policy Institute; United States. Army. (Santa Monica, CA : RAND, 2008)
Recent experiences in Iraq, Afghanistan, and the Balkans have highlighted the importance of environmental considerations. These range from protecting soldier health and disposing of hazardous waste to building water supply systems and other activities that help achieve national goals in the post-conflict phase of contingency operations. The Army has become increasingly involved with environmental issues in every contingency operation and must be better prepared to deal with them. This study assesses whether existing policy, doctrine, and guidance adequately address environmental activities in post-conflict military operations and reconstruction. Findings are based on reviews of top-level policy and doctrine, analysis of operational experience, extensive interviews with diverse Army personnel, and a review of operational documentation and literature. From these sources, a database of 111 case studies was created. The research showed that environmental concerns can have far-reaching and significant impacts on the Army, both direct and indirect, especially in terms of cost, current operations, soldier health, diplomatic relations, reconstruction activities, and the ultimate success of the operation or the broader mission. Some evidence suggests that environmental problems may have even contributed to insurgency in Iraq. Recommendations include updating current policy and doctrine to fully address environmental considerations in contingency operations; ensuring that contractors are carefully selected and managed; and transmitting proactive field environmental practices and lessons throughout the Army.
Introduction -- The context for environmental considerations in contingency operations -- Experience with environmental considerations in contingency operations -- Analysis of army operational experience -- Findings and recommendations -- Appendix A: Domestic and international law in army contingency operations -- Appendix B: The importance of environmental conditions to the local populace in Iraq -- Appendix C: Case studies of operational experiences.
"RAND Arroyo Center."
"This research was carried out in RAND Arroyo Center's Strategy, Doctrine, and Resources Program"--Pg. IV.
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Army -- Foreign service -- Environmental aspects; United States. -- Army -- Operations other than war -- Environmental aspects; Environmental policy -- United States; Environmental protection; Military doctrine -- Environmental aspects -- United States; Postwar reconstruction -- Environmental aspects